2013
DOI: 10.1089/pop.2012.0025
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Interventions in Reducing Antibiotic Use for Upper Respiratory Infections in Ambulatory Care Practices

Abstract: The objective was to evaluate the effect of separate interventions on antimicrobial prescribing for uncomplicated upper respiratory tract infections. The authors conducted a quasi-experimental pre-post study with concurrent control groups for each intervention. Academic detailing led to a significant reduction in unnecessary antibiotic prescribing. However, there was no significant change in antibiotic prescribing in response to educational mailings to providers or to provider involvement in patient mailings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
(23 reference statements)
0
30
0
Order By: Relevance
“…10 The role of antimicrobials in such a presentation is often limited to selected acute bronchitis patients with chronic obstructive pulmonary disease and asthma. 9 In our study, we found that out of 46 pharmacies which dispensed antibiotics for URTI without prescription, only 12 (26%) enquired for the presence of additional symptoms, and only 18/60 (30%) URTI pharmacies advised steam inhalation.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…10 The role of antimicrobials in such a presentation is often limited to selected acute bronchitis patients with chronic obstructive pulmonary disease and asthma. 9 In our study, we found that out of 46 pharmacies which dispensed antibiotics for URTI without prescription, only 12 (26%) enquired for the presence of additional symptoms, and only 18/60 (30%) URTI pharmacies advised steam inhalation.…”
Section: Discussionmentioning
confidence: 56%
“…However, these two are also common conditions for which unnecessary antibiotic prescription has been recorded frequently. 8,9 We selected these two conditions for this study to evaluate the extent of nonprescription dispensing of antibiotics in a Union Territory in South India. The therapeutic goal in the treatment of acute diarrhoeal illness is restoration of hydration, which is best done through oral electrolyte fluids, or intravenous fluids in case oral rehydration is not possible or contraindicated.…”
Section: Discussionmentioning
confidence: 99%
“…56 Education through academic detailing (i.e., peer-to-peer interactive educational outreach providing evidence-based material and opportunities for dialogue) is more effective than passive didactic-type education. 62 Staff should be given the opportunity to voice concerns, discuss perceived barriers to improving antibiotic prescribing practices, and adapt antibiotic stewardship policies to the needs of the dialysis facility. Effectively engaging medical directors is important for the success of these efforts and could ensure that the activities receive appropriate attention from clinical staff and leadership.…”
Section: Provide Education On Antibiotic Usementioning
confidence: 99%
“…However, the effect of educational activities is often found to be transient [ 18 ] and should be combined with active interventions. Use of rapid diagnostic tests such as the concentration of C-reactive protein as a point-of-care test, and rapid antigen detection test for group A streptococci [ 19 ], and academic detailing, or face-to-face education [ 20 ], have been found to have a positive effect on appropriate prescribing of antibiotics compared with personnel meetings and educational materials.…”
Section: Introductionmentioning
confidence: 99%